Data Literacy in the context of Information Science: analysis of undergraduate courses in Brazil - Delbianco, Natalia Rodrigues [UNESP] (2023)
Objective: Due to the development and use of technology, copious amounts of data are generated daily. With initiatives to encourage the use and reuse of data in science and business, there is a need to train, through Data Literacy, students and information professionals to make data more applicable and understandable. This research proposes a more appropriate discipline syllabus for Data Science in undergraduate Librarianship and Archival Science courses in Brazil. Methods: This research is exploratory and qualitative since it consists of selecting and collecting information about the content of the disciplines focused on Data Science in undergraduate courses in Librarianship and Archival Science in Brazil. Results: In some curricula of the 24 universities analyzed and 37 courses identified were found disciplines that may address Data Science in some way. Thus, in the Brazilian context, the most assertive action would be to include the theme Data Literacy in the context of the Data Science disciplines. Conclusions: We identified six undergraduate courses on Data Science and a lack of literature on Data Literacy, especially in Portuguese. This may be linked to the lack of disciplines, as it is still a little-discussed approach in the Information Science academic environment. The need to include Data Literacy in undergraduate courses in Brazil was perceived.